Bacterial Flora of EDTA Treated Oil ardine (Sardinella longiceps), Indian Mackerel ( Rastrelliger kanagurta) and Prawn (Metapenaeus dobsoni) in Ice Storage - SURENDRAN, P K; GOPAKUMAR, K (Fishery Technology, 2017)
The native flora of fresh oil sardine and mackerel consisted mainly of Pseudomonas spp; Moraxella spp; Acinetobacter spp. and Vibrio spp. During spoilage in ice, nearly 75% of their bacterial flora belonged to Pseudomonas spp. alone. But Na2 EDTA treatment reduced the proportion of Pseudomonas spp. considerablyand the major bacterial groups at the time of spoilage were Moraxella spp. and Acinetobacter spp. In the case of fresh prawn, the native flora were constituted by Pseudomonas spp; Moraxella spp; Acinetobacter spp. and Vibrio spp. At the time of spoilage of prawn in ice, Moraxella spp. and Acinetobacter spp. predominated, together cons1ituting 74% of the total population. Na2 EDTA treatment did not alter significantly the spoilage flora of prawns. Moraxella spp. and Acinetobacter spp. accounted for 86% of the spoilage flora in ice storage of Na2 EDTA treated prawns.